1998
DOI: 10.7863/jum.1998.17.5.333
|View full text |Cite
|
Sign up to set email alerts
|

Transperineal ultrasonographic diagnosis of vesicovaginal fistula.

Abstract: Vesicovaginal fistula is a known postoperative complication of gynecologic and obstetric abdominal and vaginal procedures. 1,2 Infrequently, vesicovaginal fistulas may result from bladder invasion by pelvic organ malignant processes. 2 We present an unusual case in which a patient with advanced vaginal squamous cell carcinoma had presenting features of urinary incontinence, vaginal bleeding, and pain. A vesicovaginal fistula was depicted by transperineal ultrasonography. CASE REPORTA 44 year old para 1 woman w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Traditionally, the imaging modalities employed to make the diagnosis of a urinary‐vaginal fistula would include intravenous pyelography, cystography and cystoscopy. It has been shown that this diagnosis can be made by transvaginal and transperineal sonography3, 4. Color Doppler with contrast media was shown to facilitate the diagnosis5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, the imaging modalities employed to make the diagnosis of a urinary‐vaginal fistula would include intravenous pyelography, cystography and cystoscopy. It has been shown that this diagnosis can be made by transvaginal and transperineal sonography3, 4. Color Doppler with contrast media was shown to facilitate the diagnosis5.…”
Section: Discussionmentioning
confidence: 99%
“…Urogenital fistula is an infrequent complication of obstetric, gynecological and urological surgery as well as of genitourinary malignancy1, 2. Abulafia et al described a case of a cancer‐related vesicovaginal fistula diagnosed by transperineal sonography3.…”
Section: Introductionmentioning
confidence: 99%